Effect of physiochemical properties in biomass-derived materials caused by different synthesis methods and their electrochemical properties in supercapacitors. Issue 21 (20th May 2021) - Zhang, Hanfang; Zhang, Yihe; Bai, Liqi; Zhang, Yingge; Sun, Li
Abstract : Effects of different synthesis methods on physicochemical properties of biomass-derived materials. Abstract : Biomass-derived carbons have drawn much attention as electrode materials for supercapacitors due to their low cost, renewability and ready availability. The inherent structure of different biomass materials greatly affects the microstructure of the obtained carbon material. Herein, we discuss in detail the effects of different activation methods, including physical activation, chemical activation etc. on the micromorphology and valence state of elements of materials. In addition, the influence of different microstructures of biomass-based carbon materials and different types of electrolytes on the electrochemical performance of supercapacitors has also been studied and summarized. Finally, the bottlenecks and future prospects of biomass-derived carbon materials are pointed out, and the corresponding coping strategies are also discussed.